Interleukin-1α and tumour necrosis factor-α modulate airway smooth muscle DNA synthesis by induction of cyclo-oxygenase-2: inhibition by dexamethasone and fluticasone propionate - Vlahos, Ross (1999)
1. Previous studies have established that glucocorticoids inhibit airway smooth muscle DNA synthesis. The effects of a combination of the pro-inflammatory cytokines, interleukin-1α (IL-1α) and tumour necrosis factor-α (TNF-α) on the inhibition of DNA synthesis by glucocorticoids in human cultured airway smooth muscle have now been investigated, since these cytokines are chronically expressed in asthmatic airways. 2. Thrombin (0.3 u ml(−1)) and basic fibroblast growth factor (bFGF, 300 pM) stimulated increases in DNA synthesis which were concentration-dependently inhibited by dexamethasone (1–1000 nM). 3. The cytokine mixture, comprising IL-1α (0.01 and 0.1 pM) and TNF-α (3 and 30 pM), directly evoked increases in DNA synthesis which were attenuated by dexamethasone. However, the cytokine mixture prevented responses to bFGF or thrombin. 4. Paradoxically, in the presence of the cytokine mixture and bFGF, dexamethasone (1–1000 nM) concentration-dependently increased DNA synthesis. Furthermore, neither dexamethasone (100 nM) nor fluticasone propionate (1 nM) inhibited DNA synthesized in response to bFGF/cytokine mixture combination and dexamethasone was similarly inactive against the thrombin/cytokine mixture. 5. The levels of prostaglandin E(2) (PGE(2)), an established inhibitor of airway smooth muscle DNA synthesis, remained below the limits of assay detection (0.05 nM) under basal conditions or following stimulation with either thrombin or bFGF. In contrast, the cytokine mixture alone, and in the presence of thrombin or bFGF, induced biologically active levels of PGE(2). Dexamethasone (100 nM), the non-selective cyclo-oxygenase (COX) inhibitor indomethacin (3 μM) or the selective COX-2 inhibitor L-745,337 (0.3 μM) completely inhibited synthesis of PGE(2). 6. Neither indomethacin (3 μM) nor L-745,337 (0.3 μM) influenced thrombin- or bFGF-induced DNA synthesis. However, each COX inhibitor enhanced DNA synthesis in cytokine-treated cells. 7. In unstimulated airway smooth muscle cells, COX-1, but not COX-2 protein was detectable by Western blotting. The induction of COX-2 protein by the cytokine mixture was attenuated by dexamethasone (100 nM), whereas the level of COX-1 protein was unaffected by either the cytokines or by dexamethasone. 8. Cytokine-induced, COX-2-dependent eicosanoid production inhibits DNA synthesis. The paradoxical increase in DNA synthesis observed in glucocorticoid treated airway smooth muscle stimulated by cytokine/bFGF combinations may be explained by the ability of glucocorticoids to repress COX-2 induction and prevent cytokine-induction of the DNA synthesis inhibitor, PGE(2).